2017
DOI: 10.5539/ijef.v9n5p132
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between FDI, Economic Growth and Financial Development in Cabo Verde

Abstract: This paper examines the relationship between foreign direct investment (FDI), economic growth and financial development in Cabo Verde for the period 1987-2014.The methodology involves the use of bound test approach to cointegration (ARDL) as well as the ECM-Granger causality analysis. The bound test indicated that there is a long-run relationship when the variable GDP and FDI are the dependent variable. Moreover, the results indicated that FDI has a positive effect on the economic growth in Cabo Verde. It also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…According to the results of the sample of the year 2008 data, it is observed that there is a two-way causality relation between economic growth and foreign direct investments. As in this study, a two-way relationship was also found in the study of Duarte et al (2017).…”
Section: International Journal Of Economic and Administrative Studiessupporting
confidence: 84%
“…According to the results of the sample of the year 2008 data, it is observed that there is a two-way causality relation between economic growth and foreign direct investments. As in this study, a two-way relationship was also found in the study of Duarte et al (2017).…”
Section: International Journal Of Economic and Administrative Studiessupporting
confidence: 84%
“…The result confirmed the expected hypothesis. Duarte et al (2017) aimed to empirical link economic growth, FDI inflow, and financial development in Cabo Verde using the dynamic ARDL for cointegration and the Granger causality test. The outcome validated that the FDI-led growth nexus is two-fold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If they are not high enough to meet the financial demand, there are also foreign sources, i.e., foreign direct investment. Their positive effect is confirmed by the boundary approach to cointegration (ARDL) as well as by the others (Duarte et al 2017). It again holds that the higher the two determinants, the more investment activity increases, and the cycle itself experiences a boom.…”
Section: Introductionmentioning
confidence: 66%